Deposition of TiN-based coatings using vacuum arc plasma in increased negative substrate bias voltage - Kuprin, A.S.; Leonov, S.A.; Ovcharenko, V.D.; Reshetnyak, E.N.; Belous, V.A.; Vasilenko, R.L.; Tolmachova, G.N.; Kovalenko, V.I.; Klimenko, I.O. (Вопросы атомной науки и техники, 2019)
The paper presents the results of the study on the influence of a high substrate bias voltage from 300 up to 1300 V on the titanium nitride coating deposition under nitrogen pressure of 2 Pa. The deposition rate, phase and chemical composition, adhesion and mechanical properties of coatings, macroparticle number and size distribution were investigated. Представлені результати дослідження впливу високої напруги зсуву підкладки від 300 до 1300 В на осадження покриттів нітриду титану при тиску азоту 2 Па. Вивчені швидкість осадження, фазовий і хімічний склад, адгезія і механічні властивості покриттів, кількість і розподіл за розмірами макрочасток. Представлены результаты исследования влияния высокого напряжения смещения подложки от 300 до 1300 В на осаждение покрытий нитрида титана при давлении азота 2 Па. Изучены скорость осаждения, фазовый и химический составы, адгезия и механические свойства покрытий, количество и распределение по размерам макрочастиц.